A new test of semantic association for use in awake craniotomy : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Wellington, New Zealand - Chapman, Jo (Massey University, 2023)
This project aimed to develop and validate a new test of non-verbal semantic association to replace the Pyramids and Palm Tree Test (PPTT) in mapping the Inferior Fronto-Occipital Fasciculus (IFOF) during awake craniotomy surgery. Research and clinical experience identified a range of problems with the PPTT, especially in its performance across cultures, and no other existing semantic test met all requirements for effective use in IFOF mapping. A new test was developed based on theoretical and clinical understandings of semantic association, using a novel item format. The final test metrics were an improvement upon the PPTT on all preselected measures of item quality. A total of 707 healthy adult participants were then recruited to complete the new test via an online survey. A final pool of 58 items were selected, all of which performed consistently as intended. Analyses of subgroup performance found there were no clinically significant gender, culture, age, or education effects on scores. These results again suggested the new test improved upon existing tests and achieved its initial design objectives. Validation then proceeded to clinical groups, but recruitment challenges meant too few participants were recruited to permit any analyses. While its validity could not be determined with this study’s data, the test and its general population norms will be available for further research and then clinical use if indicated.
Keywords: Craniotomy; Patients; Psychological testing; Neuropsychological tests; Semantic memory; 520302 Clinical psychology; 520404 Memory and attention